Intranasal administration of a synthetic TLR4 agonist INI-2004 significantly reduces allergy symptoms following therapeutic administration in a murine model of allergic sensitization - Jackson, Konner J.; Buhl, Cassandra; Miller, Shannon M.; Khalaf, Juhienah K.; Ward, Janine; Sands, Cherrokee; Walsh, Lois; Whitacre, Margaret; Burkhart, David J.; Bazin-Lee, Hélène G.; Evans, Jay T. (Frontiers in Immunology, 2024)
Introduction Atopic diseases have been steadily increasing over the past decades and effective disease-modifying treatment options are urgently needed. These studies introduce a novel synthetic Toll-like receptor 4 (TLR4) agonist, INI-2004, with remarkable efficacy as a therapeutic intranasal treatment for seasonal allergic rhinitis. Methods Using a murine airway allergic sensitization model, the impact of INI-2004 on allergic responses was assessed. Results One or two intranasal doses of INI-2004 significantly reduced airway resistance, eosinophil influx, and Th2 cytokine production – providing strong evidence of allergic desensitization. Further investigations revealed that a liposomal formulation of INI-2004 exhibited better safety and efficacy profiles compared to aqueous formulations. Importantly, the liposomal formulation demonstrated a 1000-fold increase in the maximum tolerated intravenous dose in pigs. Pre-clinical GLP toxicology studies in rats and pigs confirmed the safety of liposomal INI-2004, supporting its selection for human clinical trials. Discussion These findings lay the groundwork for the ongoing clinical evaluation of INI-2004 in allergic rhinitis as a stand-alone therapy for individuals poly-sensitized to multiple seasonal allergens. The study underscores the significance of innovative immunotherapy approaches in reshaping the landscape of allergic rhinitis management.